Optimization of Nanoclay/Polyacrylonitrile Scaffold Using Response Surface Method for Bone Differentiation of Human Mesenchymal Stem Cells. Issue 10 (October 2021) - Esmaeili, Elaheh; Malaie-Balasi, Zahra; Kabiri, Mahboubeh; Khojasteh, Arash; Mohamadyar-Toupkanlou, Farzaneh; Sadeghzadeh, Negar; ZAREI-BEHJANI, Zeinab; Hosseinzadeh, Simzar
Abstract : Response surface methodology (RSM) based on the D-optimal algorithm was employed here for the electrospinning of nanoclay/polyacrylonitrile (PAN) composite scaffold by the aim of obtaining the lower fiber diameter and better mechanical properties for bone regeneration. The input parameters included the electrospinning voltage, flow rate and the ratio of nanoclay/PAN and the obtained values for the optimum point were 17 kV for the applied voltage, 0.41 ml/hr for flow rate, and 19.06% for the nanoclay/PAN ratio. The composite scaffold was fabricated in accordance with these optimum values and then studied by scanning electron microscopy and tensile apparatus. The fiber diameter and Young's modulus of the prepared scaffold were respectively 145 ± 12 nm and 267 ± 8.7 MPa that the values were between predicted by RSM. Moreover, the biocompatibility and osteogenic differentiation of the composite scaffold were evaluated by 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide and alkaline phosphatase assays. The bare scaffold and tissue culture polystyrene were used as control groups. The results approved stronger bioactivity and bone regeneration with the composite scaffold as a presence of clay nanoparticles. Abstract : Supplemental Digital Content is available in the text.